Demographic Transition : Lessons from Bangladesh's Success Story - World Bank (Washington, DC: World Bank, 2020)
Bangladesh has been a star performer on fertility reduction, reducing its TFR from 6.7 in 1960 to 2.1 in 2017 (i.e. the replacement level of fertility). As a comparison, SSA countries reduced TFR by as little as 2 births per woman, on average, between 1970 and 2016 (World Bank, 2019), with Niger, Chad and Democratic Republic of Congo having similar levels of TFR in 2017 as they did in the 1960s. Most countries at the pre-dividend stage of the demographic transition, especially those in Africa, could learn from Bangladesh's experience. In particular, Bangladesh's fertility declines between 1975 and 1990, when it was still grappling with serious economic and social issues, were remarkable, and hold important lessons for other countries striving for similar success in optimizing their population growth. This brief case study documents how Bangladesh achieved such a rapid fertility decline despite economic constraints.